Young Khalaal Dates (Phoenix dactylifera) Effect on Blood Glucose in Alloxan-induced Wistar Male Rats - Sholikhah, Desty Muzarofatus; Wirjatmadi, Bambang; Adriani, Merryana (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Young Khalaal Dates (Phoenix dactylifera) Effect on Blood Glucose in Alloxan-induced Wistar Male Rats